Calcium dysregulation in heart diseases: Targeting calcium channels to achieve a correct calcium homeostasis - Giampaolo Morciano; Alessandro Rimessi; Simone Patergnani; Veronica A.M. Vitto; Alberto Danese; Asrat Kahsay; Laura Palumbo; Massimo Bonora; Mariusz R. Wieckowski; Carlotta Giorgi; Paolo Pinton (Pharmacological Research, 2022)
Intracellular calcium signaling is a universal language source shared by the most part of biological entities inside cells that, all together, give rise to physiological and functional anatomical units, the organ. Although preferentially recognized as signaling between cell life and death processes, in the heart it assumes additional relevance considered the importance of calcium cycling coupled to ATP consumption in excitation-contraction coupling. The concerted action of a plethora of exchangers, channels and pumps inward and outward calcium fluxes where needed, to convert energy and electric impulses in muscle contraction. All this without realizing it, thousands of times, every day. An improper function of those proteins (i.e., variation in expression, mutations onset, dysregulated channeling, differential protein-protein interactions) being part of this signaling network triggers a short circuit with severe acute and chronic pathological consequences reported as arrhythmias, cardiac remodeling, heart failure, reperfusion injury and cardiomyopathies. By acting with chemical, peptide-based and pharmacological modulators of these players, a correction of calcium homeostasis can be achieved accompanied by an amelioration of clinical symptoms.This review will focus on all those defects in calcium homeostasis which occur in the most common cardiac diseases, including myocardial infarction, arrhythmia, hypertrophy, heart failure and cardiomyopathies. This part will be introduced by the state of the art on the proteins involved in calcium homeostasis in cardiomyocytes and followed by the therapeutic treatments that to date, are able to target them and to revert the pathological phenotype.